Interfacial layer rich in organic fluoride enabling stable cycling of high-voltage PEO-based solid-state lithium batteries. (1st February 2022) - Huang, Yuli; Geng, Zhen; Sun, Guochen; Zheng, Jieyun; Li, Hong
Highlights: Organic F-rich coating layer is in-situ constructed on the surface of LiCoO2 . Side reactions of LiCoO2 and PEO are effectively suppressed. Li/LiCoO2 cells show good cycling performance at 4.2 V and 4.35 V. Designed liquid-state electrolyte plays crucial roles in forming the coating layer. Formation mechanism of the coating layer is analyzed by DFT calculations. Abstract: Solid-state lithium batteries (SSLBs) are considered as next-generation electrochemical energy storage systems with superior safety performance and high energy density. It's difficult to improve the energy density of PEO-based SSLBs, due to the limited electrochemical window. It severely hinders their applications. Here, the coating layer with organic fluoride rich microstructure is in-situ constructed on the surface of LiCoO2 by electrochemical method with a designed liquid-state electrolyte, which effectively suppresses the side reactions at the interface by physically blocking the contact between PEO and LiCoO2 . It shows improved electrochemical performance at 4.2 V and 4.35 V. In addition, this kind of method is extended to other two layered cathode materials (i.e., LiNi1/3 Co1/3 Mn1/3 O2 and LiNi0.5 Co0.2 Mn0.3 O2 ), and good battery performance is achieved as well. It indicates the universality of this method and important roles of the organic fluorides rich coating layer. The Results indicate that the designed liquid-state electrolyte plays an important role in forming organic fluoride rich coating layer. The formation mechanism of this kind of coating layer is analyzed by DFT calculations. It provides new ideas for interface protection between PEO and high-voltage layered cathode materials, meanwhile, it further improves the energy density of PEO-based SSLBs. Graphical abstract: Image, graphical abstract